Sacroiliac joint auricular surface morphology modulates its mechanical environment - Henyš, Petr; Hammer, Niels (Journal of anatomy, 2025)
The sacroiliac joint (SIJ) exhibits significant variation in auricular surface morphology. This variation influences the mechanics of the SIJ, a central node for transmitting mechanical energy from upper body to lower limbs and vice versa. The impact of the auricular surface morphology on stress and deformation in the SIJ remains poorly understood to date. Computed tomography scans obtained from 281 individuals were included to extract the geometry of the pelvic ring. Then, the auricular surface area, SIJ cartilage thickness, and total SIJ cartilage volume were identified. Based on these reconstructions, 281 finite element models were created to simulate SIJ mechanical loading. It was found that SIJ cartilage thickness only weakly depended on age or laterality, while being strongly sex sensitive. Auricular surface area and SIJ cartilage volume depended weakly and non-linearly on age, peaking around menopause in females, but without significant laterality effect. Larger SIJs, characterized by greater auricular area and cartilage volume, exhibited reduced stress and deformation under loading. These findings highlight the significant role of SIJ morphology in its biomechanical response, suggesting a potential link between morphological variations and the risk of SIJ dysfunction. Understanding this relationship could improve diagnosis and targeted treatment strategies for SIJ-related conditions.
Keywords: Young Adult; Male; počítačová rentgenová tomografie; Sacroiliac Joint; mladý dospělý; Adolescent; analýza metodou konečných prvků; mechanický stres; Adult; Biomechanical Phenomena; Aged; dospělí; sakroiliakální kloub; mužské pohlaví; senioři; mladiství; Stress, Mechanical; Tomography, X-Ray Computed; biomechanika; senioři nad 80 let; lidé; ženské pohlaví; Finite Element Analysis; Humans; Aged, 80 and over; Female; lidé středního věku; Middle Aged